THE EFFECT OF POSTER PRESENTATION TOWARDS STUDENTS' CREATIVITY AND CONCEPT COMPREHENSION ABOUT POLLUTION CONCEPT - Nugroho, Oktian Fajar (2013)
This study aims to examine the effect of poster presentation towards students' creativity and concept comprehension about pollution concept. The type of this study was weak experiment with one group pretest and postest design. Population in this research was grade 10 of senior high school students at Bina Nusantara International School Serpong consists of 10 classes. The sample has taken by using random cluster sampling technique. The quantitative data of this research has gained through concept comprehension test and observational sheet, meanwhile the qualitative data gathered through rubric and questionnaire Based on the analysis of the result, this research obtained improvement in concept comprehension with normalized gain 0,307 which was categorized into medium improvement. The correlation between students' creativity and concept comprehension done by using coefficient correlation which the result is 9%, meaning that 9% of concept comprehension may be explained by creativity. Based on the result of questionnaires about the use of poster presentation, it may be concluded that students were enjoying the use of poster presentation. Keywords : poster presentation, students' creativity, concept comprehension, achievement.